1983
DOI: 10.1099/00221287-129-10-3027
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Location of Three Mutations Impairing Penicillin Production in Aspergillus nidulans

Abstract: Three mutations impairing penicillin production in Aspergillus nidulans, npeB, npeC and npeD, have been located on linkage groups III, IV and II, respectively, and positioned relative to other loci on these chromosomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
3

Year Published

1988
1988
1995
1995

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 12 publications
1
17
3
Order By: Relevance
“…Also, mutant A. nidulans strains with altered ,-lactam-biosynthetic ability have been described (10) and characterized (20). The IPNS gene from a grampositive Streptomyces species is also of interest.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, mutant A. nidulans strains with altered ,-lactam-biosynthetic ability have been described (10) and characterized (20). The IPNS gene from a grampositive Streptomyces species is also of interest.…”
mentioning
confidence: 99%
“…Also, mutant A. nidulans strains with altered ,-lactam-biosynthetic ability have been described (10) and characterized (20 …”
mentioning
confidence: 99%
“…npeE1 prevents penicillin biosynthesis and transcription of ipnA. Quantitative ␤-Gal assays with mycelial extracts from strains BPE-1 and BPE-2 corresponding to three different times of growth (12,24, and 36 h after inoculation) confirmed that the npeE1 mutation nearly abolished expression of the ipnAЈ::ЈlacZ fusions (Fig. 4A).…”
Section: Resultsmentioning
confidence: 73%
“…involving a number of auxotrophies. An example of the difficulty in genetically analyzing regulatory mutations in this pathway is provided by the penicillin-nonproducer mutations npeC007 and npeD0045 (11), which were incorrectly assigned to chromosomes IV and II, respectively, by haploidization and meiotic linkage analysis (24). However, using more sensitive scoring techniques available for pal mutations, Shah et al (28) showed them to be palA mutant (palA is located in chromosome III) and palF mutant (palF is in chromosome VII) alleles, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation